2021
DOI: 10.7759/cureus.12586
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Relevance of Methylenetetrahydrofolate Reductase Genetic Testing in Autism: A Case Report of Successful Clinical Outcome

Abstract: Autism spectrum disorder is an emerging public health issue. The core features of autism spectrum disorder are persistent impairment in reciprocal social communication and interaction and restricted, repetitive patterns of behavior or interests. We now know that it encompasses disorders previously referred to as early infantile autism, childhood autism, Kanner autism, high-functioning autism, atypical autism, Asperger disorder, childhood disintegrative disorder, and pervasive developmental disorder not otherwi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…A case report study conducted by Fadila et al showed the effect of a three-month folic acid supplementation in a two-year-old child with a heterozygous MTHFR genetic polymorphism. The results revealed an enhancement in speech and general behavior [ 60 ]. Moreover, Gowda et al evaluated the impact of betaine, pyridoxine, folic acid, and vitamin B12 supplementation on the lowering of total homocysteine concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…A case report study conducted by Fadila et al showed the effect of a three-month folic acid supplementation in a two-year-old child with a heterozygous MTHFR genetic polymorphism. The results revealed an enhancement in speech and general behavior [ 60 ]. Moreover, Gowda et al evaluated the impact of betaine, pyridoxine, folic acid, and vitamin B12 supplementation on the lowering of total homocysteine concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, genetics plays a significant role in autism, as evidenced by the ASD occurrence rate among twins, which ranges from 36% to 95%. These genetic factors particularly influence the repetitive behavioral aspects associated with ASD [6][7][8].…”
Section: Introductionmentioning
confidence: 99%